CHALLENGES OF SOCIAL WORKERS PROVIDING SOCIAL SERVICES TO ADULT VICTIMS OF HUMAN TRAFFICKING IN SELECT SHELTERS IN SOUTH AFRICA - Botha, Renee (Social work, 2021)
Human trafficking is a global multi-million dollar industry which capitalises on the trade in human beings. It inflicts degrading experiences on its victims, hence its characterisation as modern-day slavery. This research aimed to investigate social service provision to adult victims of human trafficking in South Africa. A qualitative approach was used; data were collected using individual interviews and analysed using thematic analysis. The findings indicate that social workers faced challenges such as delays in court cases, complicated trauma, security issues and mistrust – all impacting on service delivery